Synthesis and Biological Evaluation of Some Novel Nicotinic Acid Derivatives - Ramalakshmi, N.; Aruloly, L.; Arunkumar, S.; Ilango, K.; Puratchikody, A. (Malaysian Journal of Science, 2009)
In the present study, six compounds of thiazolidinone derivatives of nicotinic acid were synthesized by reacting Schiff bases with thioglycolic acid and zinc chloride in ethanol. The Schiff bases were synthesized by treating various aromatic aldehydes with nicotinic acid hydrazide. Reaction between nicotinic acid and phosphorous pentachloride gives nicotinoyl chloride. Further nicotinoyl chloride is converted to nicotinic acid hydrazide by the action of hydrazine hydrate. Structure of these products has been established by IR, 1HNMR and Mass spectral data. The in vitro antibacterial and antifungal activities of the compounds were evaluated by paper disc diffusion method. The Minimum Inhibitory Concentration (MIC) of the compounds was also determined by agar steak dilution method. Significant antimicrobial activities were observed for some compounds of the series. Compounds were also screened for their anti-inflammatory and analgesic activity. Some of them showed comparable activity as that of the standard drug used.